2020
DOI: 10.2495/tdi-v4-n1-51-61
|View full text |Cite
|
Sign up to set email alerts
|

Regionalization of Ports as a strategic leverage to improve competitiveness: A study on central italy ports and related hinterland

Abstract: Nowadays, the success of a maritime port does not depend anymore on its traditional intrinsic points of strength, such as the internal capacity, but also on its ability to effectively integrate the development of its hinterland into business relations and supply chains. Mediterranean ports can get competitive, if specific "regionalization" processes are launched and supported. Key point for this strategy is the hinterland involvement: logistics and transports integration, railways, realization and development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…As a result, the country is facing a series of economic and social development problems, and the issue of regional economic disparities in China has thus increasingly become one of the central issues of empirical research in regional economics [27]. Regional economic disparities are mainly measured by comparing GDP or national income in a per capita sense across geographic regions [28]. Division of labor is the source of economic agglomeration, while externalities and increasing payoffs have to be the link between the role of division of labor and economic agglomeration.…”
Section: Measurement Methods Of Economic Growth Efficiencymentioning
confidence: 99%
“…As a result, the country is facing a series of economic and social development problems, and the issue of regional economic disparities in China has thus increasingly become one of the central issues of empirical research in regional economics [27]. Regional economic disparities are mainly measured by comparing GDP or national income in a per capita sense across geographic regions [28]. Division of labor is the source of economic agglomeration, while externalities and increasing payoffs have to be the link between the role of division of labor and economic agglomeration.…”
Section: Measurement Methods Of Economic Growth Efficiencymentioning
confidence: 99%
“…Based on previous research, researchers identified 15 dimensions/factors that influence the logistics system in island countries. Those dimensions/factors include demand (Zakharchuk et al, 2022), availability of raw materials (Desai & Bohara, 2021), quality of handling (Okyere et al, 2018;Elis Dwiana Ratnamurni et al, 2022), quality of documentation and logistics information (Muslimov & Shaburova, 2021), reliability of delivery time (Ehmke & Mattfeld, 2010), timing accuracy (Pendem, 2019;Chondrodima et al, 2022;Ogura et al, 2021), costs (Hasanpour Jesri et al, 2023;Cheng et al, 2022;Zakharchuk et al, 2022;Okyere, 2018), warehousing (Sivakumar, 2019), logistics infrastructure capacity (Wang, 2021), connectivity (Bevilacqua, 2022;Pistilli, 2020), services (Anas et al, 2020;Sadowska et al, 2020;Bazaras et al, 2023), institutional (Yashin et al, 2023), competence (Dwijaya Saputra & Kusnadi, 2021Zamkova et al, 2023), education and training (Liu & Yang, 2023), automation (Singh, 2018;Song, 2021).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%